Healthcare workers' attitudes towards hand-hygiene monitoring technology. Issue 4 (August 2019) - Tarantini, C.; Brouqui, P.; Wilson, R.; Griffiths, K.; Patouraux, P.; Peretti-Watel, P.
Summary: Background: Automated radio-frequency identification (RFID)-based hand-hygiene monitoring technology was implemented in an infectious disease department to study healthcare workers' (HCWs') practices and to improve hand hygiene. Aim: To assess HCWs' attitudes towards this innovative monitoring device in order to anticipate resistance to change and facilitate future implementation. Methods: In-depth interviews and an ethnographic approach. Findings: From the perspective of HCWs, while they recognize the usefulness of RFID technology to prevent the transmission of infections to patients, they expressed concerns about risks related to RFID electromagnetic waves, as well as control by their superiors. Overall, HCWs' opinions oscillated between positive feelings characterized by enthusiasm for the possibility of changing their practices using technologies and research, and negative feelings marked by strong criticisms of these technologies and research. These criticisms included blaming hand-hygiene monitoring technology for decontextualizing HCWs' practices. They perceived the technologies through the prism of the local and national contexts in which they are embedded. From their point of view, technologies are primarily in the best interests of the project team. Thus, they affirm and maintain the different interests and objectives between themselves and the project team, crystallizing a conflict of professional norms and values between these two groups. The forms of resistance taken by HCWs were practical as well as oral. Conclusion: Innovative technologies should be developed to address HCWs' attitudes surrounding RFIDs. It is crucial to inform HCWs about the nature of these technologies, although some criticisms about monitoring systems are based on more structural causes.